The Localization of Interfirm Transaction Relationships - Kentaro Nakajima; Yukiko Saito; Iichiro Uesugi (European Regional Science Association (ERSA), 2012)
Using a unique dataset of more than 140,000 manufacturing firms in Japan containing information on their suppliers and customers, this paper looks at the physical distances be- tween transaction partners to examine the localization of transaction relationships. We find the following. First, ntrols for the location of firms and their potential partners, transaction relationships in about 90-95% of the 150 three-digit manufacturing industries can be labelled as localized at distances of 40km or less. This indi- cates that physical distance is a key factor in firmsf choice of transaction partners. Second, based on a counterfactual that controls for the average distance of transaction relationships in the manufacturing sector as a whole, we find that in about 40% of industries transaction relationships are localized at short distances of up to 40km. Third, the extent of industrial localization and the extent of the localization of transaction relationships are positively cor- related. However, there are a number of exceptions and we provide potential explanations for these.
Keywords: 330